Combined density functional theory and molecular dynamics study of Sm0.75A0.25Co1−xMnxO2.88 (A = Ca, Sr; x = 0.125, 0.25) cathode material for next generation solid oxide fuel cell. Issue 2 (12th December 2019) - Olsson, Emilia; Cottom, Jonathon; Aparicio-Anglès, Xavier; de Leeuw, Nora H.
Abstract : Computational study of novel next-generation SOFC cathode Sm0.75 (Ca, Sr)0.25 Mn x Co1− x O2.88 showing fast electronic and ionic conduction in bulk. Abstract : One of the main challenges facing solid oxide fuel cell (SOFC) technology is the need to develop materials capable of functioning at intermediate temperatures (500–800 °C), thereby reducing the costs associated with SOFCs. Here, Sm0.75 A0.25 Mn x Co1− x O2.88 (A = Ca, or Sr) is investigated as a potential new cathode material to substitute the traditional lanthanum–strontium manganate for intermediate temperature SOFCs. Using a combination of density functional theory calculations and molecular dynamics simulations, the crucial parameters for SOFC performance, such as the electronic structure, electronic and ionic conductivity, and thermal expansion coefficient, were evaluated. An evaluation of the results illustrates that the conductivity and thermal match of the materials with the electrolyte is dramatically improved with respect to the existing state-of-the-art.